A Study on the Inflammatory Response of the Brain in Neurosyphilis - Qiyu Zhang; Jie Ma; Jia Zhou; Hanlin Zhang; Mansheng Li; Huizi Gong; Yujie Wang; Heyi Zheng; Jun Li; Ling Leng (Advanced Science)
Abstract Neurosyphilis (NS) is a clinical condition caused by infection of the central nervous system (CNS) by Treponema pallidum (Tp) that can lead to asymptomatic meningitis and more serious neurological diseases, such as dementia and blindness. However, current studies on the pathogenesis of NS are limited. Here, through the integration analysis of proteomics and single‐cell transcriptomics, Toll‐like/NF‐κB signaling is identified as the key pathway involved in CNS damage caused by Tp. Moreover, monocyte‐derived macrophages are key cells involved in the inflammatory response to Tp in the CNS of NS patients. In addition, it is found that inflammatory cells in peripheral blood may cause neurological damage through disruption of the blood‒brain barrier (BBB) in individuals with NS. Notably, activation of the Toll‐like/NF‐κB signaling pathway, as well as dysregulation of neural function, is likewise validated in an in vitro NS brain organoid model. In conclusion, the results revealed the mechanisms of inflammation‐mediated brain injury in Tp‐induced NS and provided new ideas for the clinical treatment of Tp infection.